AQP2 as a target of lycopene protects against atrazine-induced renal ionic homeostasis disturbance. Issue 11 (7th May 2021) - Guo, Jian-Ying; Lin, Jia; Huang, Yue-Qiang; Talukder, Milton; Yu, Lei; Li, Jin-Long
Abstract : This study shows that atrazine exposure can lead to nephrotoxicity by interfering with ion homeostasis. Lycopene maintains ion homeostasis by regulating the expression of AQPs and the activity of ATPase, and antagonizes the nephrotoxicity induced by atrazine. Abstract : Atrazine (ATR), a ubiquitous environmental contaminant in water and soil, causes environmental nephrosis. To reveal the toxic effect of ATR on the kidney and the potential chemical nephroprotective effect of lycopene (LYC), Kun-Ming mice of specific pathogen-free (SPF) grade were treated with LYC (5 mg kg −1 ) and/or ATR (50 mg kg −1 or 200 mg kg −1 ) for 21 days. The degree of renal injury was evaluated by measuring the ion concentration, ATPase activities and the mRNA expressions/levels of associated ATPase subunits. In addition, the expression of renal aquaporins (AQPs) was analyzed. The results showed that the renal tubular epithelial cells of ATR-exposed mice were swollen, the glomeruli were significantly atrophied, and the ion concentrations were obviously changed. The activity of Na + –K + –ATPase and the transcription of its subunits were downregulated. The activity of Ca 2+ –Mg 2+ –ATPase and the transcription of its subunits were upregulated. The expression of AQPs, especially the critical AQP2, was affected. Notably, ATR-induced nephrotoxicity was significantly improved by LYC supplementation. Therefore, LYC could protect the kidney against ATR-induced nephrotoxicity via maintaining ionic homeostasis, reversing the changes in ATPase activity and controlling the expression of AQPs on the cell membrane. These results suggested that AQP2 was a target of LYC and protected against ATR-induced renal ionic homeostasis disturbance.